The Nationalism Values in Pupuh Lyrics for Elementary School Students - Suherman, Agus; Suharno, Suharno (International Conference on Elementary Education, 2020)
The Instilling of nationalism values should be carried out earlier, especially when the children are still at elementary school age. The sources of national values come not only from the ideal and constitutional foundation, but also can be drawn from subjects' content at school. By Using a descriptive method, this paper examined national values contained in pupuh lyrics for elementary school students in Sundanese language subjects. As a result, some pupuh that are taught at several different class levels contain many nationalism values. These values have long been embraced and practiced by Sundanese people so that it has become a collective memory in carrying out daily life. In addition, these values are in accordance with the four pillars of our nationality i.e. Pancasila, the 1945 Constitution, NKRI and Bhineka Tunggal Ika. Therefore, Sundanese language lessons especially pupuh material greatly contribute in instilling national values to the next generation of the nation